91 Key Economic and Marketing Trends in fed Cattle and High-Quality Beef. (21st September 2022) - McCullock, Katelyn; Robb, James
Abstract: This presentation provides a descriptive overview of economic and marketing trends and key changes in cattle feeding over the last two decades. The focus will highlight four major areas: aspects of beef demand (domestic and foreign), market-driven carcass characteristics, economically driven producer production trends, and marketing arrangements. The last two decades have brought unique challenges and opportunities to the beef industry through demand changes and production technologies. Consumer diet trends, the rise and fall of saturated fat, and the expansion into the global marketplace have all shaped the beef demand profile. New technologies also have shaped feedlot management and marketing. Over the last two decades, changes have revolutionized fed cattle marketing, rewarding quality through alternative marketing arrangements, especially formula pricing, including grid pricing. Evolutionary changes have been seen in carcass grading characteristics (e.g., Choice/Select price spread) and helped focus production practices to zero in on producing higher-quality beef. Trends at the feedlot such as carcass weights, days on feed, and other productivity measures have also been shaped by in-part by economics. Last, we will offer a few comments on emerging issues and trends.